Bipolar disorder and Susac syndrome: a case report. (15th July 2021) - Gutiérrez-Arango, Felipe; Anmella, Gerard; Hidalgo-Mazzei, Diego; Gomes-da-Costa, Susana; Gil-Badenes, Joaquín; Marco-Hernández, Javier; Espinosa, Gerard; Colomer, Lluc; Baldaquí, Nuria; Pujal, Ester; Fico, Giovanna; Giménez, Anna; et al.
Abstract : Susac-syndrome is a rare autoimmune disease that manifests with mood alterations in up to 15% of cases and is usually treated with corticosteroids. We present the case of a 41-year-old woman with a first manic episode and history of Susac-syndrome, secondary Cushing's syndrome after receiving high doses of corticosteroids and a previous depressive episode. Differentiating between primary and secondary mania is difficult, as people with bipolar disorder are prone to multiple psychiatric and nonpsychiatric comorbidities, in this case, the differential diagnosis included secondary mania, corticoid-induced manic episode and primary bipolar disorder. Upon admission, corticosteroid treatment was suspended, and the patient was started on lithium and risperidone. Secondary causes of mania were discarded and, assessing temporal and dosage criteria, it was deemed unlikely that the present episode was corticosteroid-induced. One-year outpatient follow-up pointed towards a primary bipolar type I disorder, as a separate entity from her Susac-syndrome. Corticosteroid use or abrupt withdrawal pose an underestimated risk of inducing depressive or manic symptoms, which may unmask affective disorders in susceptible individuals. Many medical conditions share CNS involvement and/or high-dose/prolonged corticosteroid treatment. In such cases, psychiatric manifestations such as mania or depression should be regarded as secondary and studied to determine the existence of medical complications before considering primary psychiatric conditions.